2023
DOI: 10.1021/acs.orglett.3c01474
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Activated Nickel Thiolates for C–S Couplings

Guohua Wang,
Lei Gao,
Yunhui Feng
et al.

Abstract: Thiolates are known as the inhibitors of metal catalysis due to their strong coordination with the metal. Herein, we reported visible-light-induced homolysis of the Ni–S bond to activate the nickel(II) thiolates for the C–S coupling, obviating the use of exogenous photocatalysts and other additives. Various aryl bromides/iodides can efficiently couple with thiols with a wide range of functional groups under mild conditions. Preliminary mechanistic studies suggested the homolysis of the Ni–S bond is the key ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The Ni­(I)­SR complex can then undergo oxidative addition into an aryl iodide to form a Ni­(III)­SR­(X)Ar complex, which, upon reductive elimination, delivers the desired thioether product and a Ni­(I)­X species. This proposed mechanism has since been validated by several groups and invoked in other C–heteroatom cross-coupling reactions. The electrochemical versions of this Ni-catalyzed C–S cross-coupling reaction have since been reported. , …”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The Ni­(I)­SR complex can then undergo oxidative addition into an aryl iodide to form a Ni­(III)­SR­(X)Ar complex, which, upon reductive elimination, delivers the desired thioether product and a Ni­(I)­X species. This proposed mechanism has since been validated by several groups and invoked in other C–heteroatom cross-coupling reactions. The electrochemical versions of this Ni-catalyzed C–S cross-coupling reaction have since been reported. , …”
Section: Introductionmentioning
confidence: 70%
“…This is especially the case in drug discovery, as medicinal chemistry is often performed across electron-rich benzenes and electron-deficient heterocycles with a wide range of alkyl and heteroatomic fragments. Over the past decade, several general strategies toward C­(sp 2 )–C­(sp 3 ), ,,,,,,,, C­(sp)–C­(sp 3 ), ,, and C-heteroatom ,,,,,, cross-couplings have been enabled by photo- and electrochemistry. , Throughout our experience in developing Ni-catalyzed photo- and electrochemically driven C–C and C–heteroatom cross couplings, we, as well as others, have noticed several reactivity trends . To aid the community in discerning the appropriate tactic, we have assembled a user guide to help navigate photo- and electrochemically driven cross-coupling reactions and highlight useful technologies developed by others in the field (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the cross-coupling of aryl thiols with organic halides or pseudohalides proceeded via S–H bond cleavage 6 with the aid of a transition metal catalyst ( e.g. , rhodium, 7 copper, 8 palladium, 9 cobalt, 10 and nickel 11,12 ) or a photocatalyst 13 in the presence of a base (Scheme 1a), leading to the corresponding aryl sulfides as the final products while leaving the C–S bond in the thiol substrate intact. It was reported that even under reductive conditions that are commonly employed in cross-electrophile couplings by using nickel or cobalt as the transition metal catalyst and zinc as the reducing metal (Scheme 1b), 10,12 the cross-coupling of aryl thiols with aryl halides still produced the corresponding aryl sulfides instead of biaryls as the target products.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our overarching strategies to synthesize a diverse range of thio-based bioactive compounds ( I –VI ), encompassing thioether, thioester, and dithioester derivatives, we recognized the potential of thiophosphonium salts as versatile core scaffolds for these molecules (Scheme B). …”
mentioning
confidence: 99%
“…To this end, various representative applications were conceived for these valuable salts 3 as depicted in Scheme and . For instance, we conducted selective reduction and oxidation protocols of the C– + P, enabling the synthesis of the valuable thioether, deuterated-thioether, thioester, and dithioester derivatives. ,,, …”
mentioning
confidence: 99%